Adoption Intensity of Selected Organic-Based Soil Fertility Management Technologies in the Central Highlands of Kenya - Mwaura, George G.; Kiboi, Milka N.; Bett, Eric K.; Mugwe, Jayne N.; Muriuki, Anne; Nicolay, Gian; Ngetich, Felix K. (Frontiers in Sustainable Food Systems, 2021)
Soil fertility decline continues to be a major challenge limiting agricultural productivity globally. Despite the novelty of organic-based technologies in enhancing agricultural production in Kenya's central highlands, adoption is low. Therefore, we carried out a cross-sectional household survey of 300 randomly selected smallholder farmers to determine the specific organic-based practices by farmers; and the socioeconomic factors that influence the adoption intensity of selected organic-based technologies. We used descriptive statistics to summarise the data and the Tobit regression model to evaluate the socioeconomic determinants of adoption intensity of selected organic-based technologies. We identified nine organic-based technologies that had different adoption rates among the farmers. The majority of the farmers had adopted manure (97%) and manure combined with fertiliser (92%) in Murang'a and Tharaka-Nithi, respectively. Manure was applied to the largest land in Murang'a with 31% of the cultivated land. In comparison, manure combined with fertiliser had the highest adoption intensity in Tharaka-Nithi applied to about 25% of the cultivated land. Gender, age of the household head, level of education, household size, access to external labour, training, Tropical Livestock Unit, agriculture group membership, access to credit, land cultivated, and farming experience influenced the adoption intensity of organic-based technologies among smallholder farmers. Based on the smallholder farmers' adoption behaviour, this study can be used to disaggregate the farming households better in order to tailor specific organic-based soil fertility technologies solutions that meet their unique needs. One group would be those households that face specific constraints, as reflected in their low adoption rates, women-headed households and older farmers, and thus require more targeted / intensive efforts to overcome these barriers. The other group would be those households that require less focus because, when confronted with the technologies, they are more likely to adopt them easily, for example, the male-headed households. Hence, the smallholder farmers' adoption behaviour, can enable policymakers to form a base for designing appropriate policies that encourage the adoption of organic-based soil fertility technology by smallholder farmers.